2012
DOI: 10.1155/2012/534929
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Type I Interferon Production: A New Therapeutic Option to Reduce the HIV-1-Induced Immune Activation

Abstract: Highly active antiretroviral therapy has dramatically improved the morbidity and mortality of HIV-1-infected individuals. A total of 25 licensed drugs provide the basis for an optimized virus-suppressive treatment of nearly each subject. The promises of immune reconstitution and normal life expectancy, however, fall short for a number of patients, either through inadequate recovery of CD4+ T-cell counts or the occurrence of non-AIDS defining malignancies. In this respect, the prevalence of Epstein-Barr virus-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 93 publications
1
18
0
1
Order By: Relevance
“…An earlier report by Pritschet et al found a crucial role for CD4, but not BDCA-2, in HIV endocytosis, although those confocal microscopy experiments were not quantitative (48). It is possible that BDCA-2, by binding HIV, increases the efficiency of CD4-dependent HIV endocytosis (49). Moreover, our data suggest an egress of precursor pDCs during acute SIVagm infection, similar to what has been reported for SIVmac infection (24,33).…”
Section: Discussionsupporting
confidence: 78%
“…An earlier report by Pritschet et al found a crucial role for CD4, but not BDCA-2, in HIV endocytosis, although those confocal microscopy experiments were not quantitative (48). It is possible that BDCA-2, by binding HIV, increases the efficiency of CD4-dependent HIV endocytosis (49). Moreover, our data suggest an egress of precursor pDCs during acute SIVagm infection, similar to what has been reported for SIVmac infection (24,33).…”
Section: Discussionsupporting
confidence: 78%
“…Curiously, these factors are not induced by interferon-α treatment in vivo , in contrast to the majority of recognized anti-HIV-1 restriction factors [28]. This regulatory feature may be pertinent to the development of interventions to attenuate HIV-associated inflammation and immune activation through the blockade of type I interferon signaling [40], as interferon-α blockade may not compromise the viral control mediated by these particular factors. The molecular biology and cellular roles of the p21 and SLFN11 factors have been extensively characterized, providing key insights into the mechanisms underlying our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune disorders including multiple sclerosis, rheumatic disease, asthma, and allergies are also associated with high rates of neuropsychiatric symptoms and depression (Pollak and Yirmiya, 2002). Similarly, patients with human immunodeficiency virus (HIV), which is associated with increased inflammatory cytokine production, and particularly interferon (IFN)-alpha (Ries et al, 2012), manifest neuropsychiatric complications, such as cognitive decline and psychomotor disturbance, and often depression and fatigue (Treisman et al, 1998, Wojna et al, 2006, Payne et al, 2012). These data suggest that innate immune activation during chronic medical illnesses, as characterized by elevations in inflammatory cytokines, may contribute to the high rates of depression and other neuropsychiatric (e.g.cognitive or psychomotor) symptoms observed in medically ill populations.…”
Section: Cytokines and Depressionmentioning
confidence: 99%